Fear of crime in an oil boomtown in Western North Dakota. Issue 4 (8th August 2018) - Mrozla, Thomas; Dahle, Thorvald O.; Huynh, Carol; Robinson, Chloe; Archbold, Carol A.; Marcel, Alexandra
Abstract: There is limited published research that centers on the fear of crime in communities that have experienced rapid population growth because of increased energy production or an 'energy boom'. This study examines fear of crime among residents living in an oil boomtown in the Bakken region in western North Dakota. This study is unique as it utilizes a measure of change in residents' fear of crime resulting from the oil boom in western North Dakota. The main data source for this study includes surveys completed by a random sample of residents living in Williston, North Dakota ( n  = 380) during the fall of 2015. Williston is considered the epicenter of the oil boom in the Bakken region, and experienced significant changes in population size and composition because of the rapid population growth associated with the oil boom. Findings reveal that personal safety is a significant predictor of general fear of crime, violent crime, property crime, and changes in fear of crime.